Detrital Zircons in Crustal Evolution: A Perspective from the Indian Subcontinent - Kumar Batuk Joshi; Upasana S. Banerji; Chandra Prakash Dubey; Elson P. Oliveira (Lithosphere, 2022)
AbstractDetrital zircons are frequently used for crustal evolutionary studies as they sample vast regions of the continental crust. In the present study, we utilise newly compiled U-Pb detrital zircon data from the Indian subcontinent as well as a compilation of previously reported global data along with Hf isotopes of modern and ancient sediments in order to understand crustal evolution in the Indian subcontinent. The detrital zircon U-Pb age data from the Indian subcontinent show peaks (at 2400–2700, 1600–1900, 850–1200, and 450–550 Ma) that correlate with the formation of major known supercontinents. In addition, two other peaks at 3200–3400 Ma and <100 Ma do not correspond to periods of supercontinent formation. The former peak may represent uneven geographic sample density due to enhanced erosion and exhumation of Archean sources. The distinctly younger (<100 Ma) detrital zircon age peak may represent zircon preservation due to the Himalayan orogeny. The zircon Hf model ages from the Indian subcontinent suggest that the Precambrian crust was the major source of continental crust with younger ages. The conspicuous shift to positive εHf (t) at ca. 3600 Ma from detrital zircons of the Indian subcontinent may underscore a change in geodynamic processes, while the highly negative values post ~3200 Ma may be associated with the crustal reworking. A wavelet analysis of detrital zircons from the Indian and global databases reveals a prominent cyclicity of ~800 Myr and ∼350 Myr plausibly representing the supercontinent cycle and its half cycle. An incongruence in power between global and Indian εHf (t) could be due to the local subcontinental geologic processes during the Paleo- to Mesoarchean.